Validation of a Monte Carlo code system for grid evaluation with interference effect on Rayleigh scattering. (2nd February 2018) - Zhou, Abel; White, Graeme L; Davidson, Rob
Abstract: Anti-scatter grids are commonly used in x-ray imaging systems to reduce scatter radiation reaching the image receptor. Anti-scatter grid performance and validation can be simulated through use of Monte Carlo (MC) methods. Our recently reported work has modified existing MC codes resulting in improved performance when simulating x-ray imaging. The aim of this work is to validate the transmission of x-ray photons in grids from the recently reported new MC codes against experimental results and results previously reported in other literature. The results of this work show that the scatter-to-primary ratio (SPR), the transmissions of primary ( T p ), scatter ( T s ), and total ( T t ) radiation determined using this new MC code system have strong agreement with the experimental results and the results reported in the literature. T p, T s, T t, and SPR determined in this new MC simulation code system are valid. These results also show that the interference effect on Rayleigh scattering should not be neglected in both mammographic and general grids' evaluation. Our new MC simulation code system has been shown to be valid and can be used for analysing and evaluating the designs of grids.